Antinociceptive and anticonvulsant effects of the monoterpene linalool oxide - Flávia Negromonte Souto-Maior; Diogo Vilar da Fonsêca; Paula Regina Rodrigues Salgado; Lucas de Oliveira Monte; Damião Pergentino de Sousa; Reinaldo Nóbrega de Almeida (Taylor & Francis Group, 2017)
Context: Linalool oxide (OXL) (a monoterpene) is found in the essential oils of certain aromatic plants, or it is derived from linalool. The motivation for this work is the lack of psychopharmacological studies on this substance. Objective: To evaluate OXL's acute toxicity, along with its anticonvulsant and antinociceptive activities in male Swiss mice. Material and methods: OXL (50, 100 and 150 mg/kg, i.p.) was investigated for acute toxicity and in the Rota-rod test. Antinociceptive activity was evaluated by the acetic acid-induced writhing test, and by formalin testing. Anticonvulsant effects were demonstrated by testing for pentylenetetrazol (PTZ)-induced seizures and by Maximum Electroshock headset (MES) test. OXL was administered to the animals intraperitoneally 30 min before for pharmacological tests. Results: OXL showed an LD50 of ∼721 (681-765) mg/kg. In the Rota-rod test, it was observed that OXL caused no damage to the animal's motor coordination. OXL significantly reduced (p < .001) the number of writhings. OXL also significantly decreased (p < .05, p < .01 or p < .001) paw-licking time in the two phases of the formalin test. OXL significantly reduced (p < .01 or p < .001) the duration of tonic seizures in the MES test, and at the dose 150 mg/kg, significantly increased (p < .01) the latency to first seizure in the PTZ test. Conclusion: The tested doses of OXL were safe, with no motor impairment, and show clear antinociceptive and anticonvulsant potential. Future investigations with this monoterpene may lead to the development of a new molecule with even higher potency and selectivity.